1977
DOI: 10.1002/1097-0142(197703)39:3<1229::aid-cncr2820390331>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Familial occurrence of colon and uterine carcinoma and of lymphoproliferative malignancies.II. Chromosomal and immunologic abnormalities

Abstract: Cytogenic and immunologic studies were performed on 20 members of a family who had an increased susceptibility to carcinomas of the colon, uterus and of lymphoproliferative malignancy. Chromosomal abnormalities such as small G and/or long submetacentric marker chromosome and other aberrations were observ.ed in members who had cancer as well as some asymptomatic siblings. In addition, impairment of T cell function was noted in many of the members suggesting that defective cell-mediated immunity, which also may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…255,256,269 Development of lymphoid tumors such as ALL, CLL, and malignant lymphomas was also reported in human HNPCC kindreds. [270][271][272][273] These observations imply that defects in the mismatch repair apparatus may cause accumulation of mutations in key oncogenes or tumor suppressor genes as well as in microsatellite sequences, thus contributing to the development of tumors. 250,251,274 However, the proportion and spectrum of sporadic cancers associated with mutations in mismatch repair genes has not been clearly elucidated at this time.…”
Section: Role Of Dna Mismatch Repair Genesmentioning
confidence: 99%
“…255,256,269 Development of lymphoid tumors such as ALL, CLL, and malignant lymphomas was also reported in human HNPCC kindreds. [270][271][272][273] These observations imply that defects in the mismatch repair apparatus may cause accumulation of mutations in key oncogenes or tumor suppressor genes as well as in microsatellite sequences, thus contributing to the development of tumors. 250,251,274 However, the proportion and spectrum of sporadic cancers associated with mutations in mismatch repair genes has not been clearly elucidated at this time.…”
Section: Role Of Dna Mismatch Repair Genesmentioning
confidence: 99%
“…It has been reported that the development of lymphoma or leukemia is uncommon in HNPCC kindreds, and its relative risk is estimated as low. 8,9 However, lymphocytic neoplasms have been observed in patients with Lynch syndrome Type II 12,13 in addition to those with Muir-Torre syndrome (MTS) [28][29][30][31] and Turcot's syndrome 32 (Table 2); the latter two syndromes have been determined to be distinct phenotypes of HNPCC. The MTS 33, 34 is clinically characterized by the association of sebaceous gland tumors (adenoma, epithelioma, or carcinoma) with cancer(s) of internal organs, including the colon and rectum.…”
Section: Discussionmentioning
confidence: 99%
“…32 The hematologic malignancies associated with HNPCC and its related syndromes include lymphocytic leukemia, both acute and chronic, nonHodgkin's lymphoma, and lymphosarcoma ( Table 2). [11][12][13][28][29][30][31][32] The reported case of Burkitt's lymphoma 13 is exceptional in that this type of lymphoma is believed to result, at least in part, from Epstein-Barr virus infection and thus is not likely to be related to the HNPCC syndrome. Of 19 HNPCC kindreds in which hematologic neoplasms were diagnosed, only four patients, including our patient, presented with colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations